In VIVO anti-tumor activities of gelatin - Inamura, Y.; Koide, T.; Kojima, T.; Nagata, H.; Ito, N.; Suzumura, K.; Hashimoto, Y. (Experimental Oncology, 2009)
Aim: As reported previously, porcine skin gelatin exerted direct anti-tumor effect in vitro and induced anti-tumor peritoneal macrophages in vitro. The present study investigated whether or not the gelatin exerted anti-tumor effect in vivo. Methods: In vitro anti-tumor activities of peritoneal macrophages and the gelatin were evaluated with tritium thymidine uptake by target tumor cells. In vivo anti-tumor activity was evaluated with the survival of tumor-bearing animals and the size of the tumor. Results: Intraperitoneal daily administration of 12.5 mg of the gelatin prolonged the survival of mice which had been intraperitoneally inoculated with MH134 (hepatic cell carcinoma cell line) or Colon 26 (colon carcinoma cell line) tumor cells, and there were no tumors in case of MH134 cells inoculation. Intraperitoneal daily administration of 12.5 mg of the gelatin did not affect growth of subcutaneous MH134 tumor. The gelatin administered subcutaneously did not affect the survival of mice with intraperitoneal MH134 tumor. On the other hand, bovine skin gelatin administered subcutaneously achieved statistically significant prolongation of the survival. The contact of MH134 cells with porcine skin gelatin for 5 min was required for the gelatin to exert its anti-tumor activity in vitro. Porcine skin gelatin of 12.5 mg injected intraperitoneally was detected as protein in the peritoneal cavity 5 min after the injection. Peritoneal macrophages elicited by intraperitoneal injection with porcine skin gelatin suppressed tritium thymidine uptake by MH134 cells more strongly than those elicited by thioglycollate injection. Conclusion: Porcine skin gelatin administered intraperitoneally prolonged the survival of tumor-bearing mice via activation of peritoneal macrophages and involvement of direct anti-tumor activity of porcine skin gelatin. Key Words: porcine skin, gelatin, dissemination.